2019
DOI: 10.1002/jbio.201900167
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging of the human placental vasculature

Abstract: Minimally invasive fetal interventions require accurate imaging from inside the uterine cavity. Twin-totwin transfusion syndrome (TTTS), a condition considered in this study, occurs from abnormal vascular anastomoses in the placenta that allow blood to flow unevenly between the fetuses. Currently, TTTS is treated fetoscopically by identifying the anastomosing vessels, and then performing laser photocoagulation. However, white light fetoscopy provides limited visibility of placental vasculature, which can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 63 publications
1
38
0
Order By: Relevance
“…For PA follicle density evaluation, we used the 850 nm LED light source (longer wavelength, higher penetration depth). These maps are similar to previous studies that showed vascularity using PAI [ 47 , 48 , 49 ].…”
Section: Resultssupporting
confidence: 90%
“…For PA follicle density evaluation, we used the 850 nm LED light source (longer wavelength, higher penetration depth). These maps are similar to previous studies that showed vascularity using PAI [ 47 , 48 , 49 ].…”
Section: Resultssupporting
confidence: 90%
“…A backward-mode FP interferometer (FPI) has also been developed to achieve high-resolution all-optical PAT, ( Figure 14 a) [ 145 , 146 , 147 ]. The FPI sensor head has a planar polymer (Parylene C) film spacer, which is sandwiched by two dichroic mirrors.…”
Section: All-optical Detection Reflection-mode Photoacoustic Micromentioning
confidence: 99%
“…When the thickness of the polymer is changed by the incident PA pressure, the reflectance intensity would be modulated, and thus the amplitude of PA signals can be detected. By using the FPI-based PAM system, researchers have demonstrated in vivo imaging for human palm vasculature [ 148 , 149 ], human peripheral limb arteries [ 150 ], mouse brain vasculature [ 146 ], and human placental vasculature [ 147 ]. Optical fiber-based FPIs have also been developed with high sensitivity, broadband, small footprint, and wide detection angels [ 151 , 152 , 153 ].…”
Section: All-optical Detection Reflection-mode Photoacoustic Micromentioning
confidence: 99%
“…51 New methods such as photoacoustic imaging, which can be incorporated into current fetoscopes, can also be used to enhance the identification of placental vessels to improve success of ablation. 52 Thus, while we have seen advances in data collection to demonstrate likely maternal complication rates, more needs to be done in this area to help determine the optimal approaches, including longterm outcome studies. In addition, as we see new technologies being applied, we must ensure good, (randomised) prospective trials are performed to obtain objective evidence of the best approaches to use.…”
Section: Advances In Fetal Theraphymentioning
confidence: 99%
“…An early application is likely to be in the treatment of twin‐to‐twin transfusion syndrome where a combination of Doppler and MRI are used to determine placenta and vascular structure, and, using computer vision and deep learning techniques, the ideal entry point and the laser trajectory can be determined . New methods such as photoacoustic imaging, which can be incorporated into current fetoscopes, can also be used to enhance the identification of placental vessels to improve success of ablation …”
Section: Advances In Fetal Theraphymentioning
confidence: 99%